1997
DOI: 10.1002/(sici)1097-0290(19970605)54:5<416::aid-bit2>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic studies of Chromobacterium viscosum lipase in AOT water in oil microemulsions and gelatin microemulsion-based organogels

Abstract: Kinetic studies have shown that octyl decanoate synthesis by Chromobacterium viscosum (CV) lipase in sodium bis‐2‐(ethylhexyl) sulfosuccinate (AOT) water in oil (w/o) microemulsions occurs via the nonsequential (ping‐pong) bi bi mechanism. There was evidence of single substrate inhibition by decanoic acid at high concentrations. Initial rate data yielded estimates for acid and alcohol Michaelis constants of ca. 10−1 mol dm−3 and a maximum rate under saturation conditions of ca. 10−3 mol dm−3 s−1 for a lipase c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
3

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 34 publications
(3 reference statements)
0
17
0
3
Order By: Relevance
“…The same mechanism has been proposed for esterification or transesterification reactions catalyzed by both free lipases in microemulsions [47] as well as immobilized lipases (lipozyme) in non-polar organic solvents [48] and scCO 2 [49]. Furthermore, it has also been suggested for lipases immobilized in MBGs [13,24].…”
Section: Kinetic Analysismentioning
confidence: 56%
See 1 more Smart Citation
“…The same mechanism has been proposed for esterification or transesterification reactions catalyzed by both free lipases in microemulsions [47] as well as immobilized lipases (lipozyme) in non-polar organic solvents [48] and scCO 2 [49]. Furthermore, it has also been suggested for lipases immobilized in MBGs [13,24].…”
Section: Kinetic Analysismentioning
confidence: 56%
“…The preparation of MBGs was first reported in 1986 [6][7][8] and subsequent spectroscopic investigations [9,10] have shown that the microemulsion structure is well preserved in the network of the gels, which are believed to contain a more or less bicontinuous phase that may co-exist with conventional w/o microemulsion droplets. MBGs containing immobilized lipase were applied for the preparative scale synthesis of miscellaneous esters and both regio-and stereoselectivity have been observed [11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…In aqueous solutions E a is an intrinsic feature of the enzyme itself (Jenta et al 1997). However, immobilizing the enzyme, diffusion may become rate limiting and the reaction may switch from kinetic to diffusion controlled resulting in a change in the measured apparent E a .…”
Section: Activation Energymentioning
confidence: 99%
“…They found that both the activity of Chromobacterium viscosum lipase (CV-lipase) and the interfacial concentration of water, [H 2 O] i (28.1-31.8 M) [33] were essentially unchanged across W 0 = 12-44. Presumably, the scarcity of [H 2 O] i (almost half of the bulk water concentration) with remarkably high interfacial concentration (8.1-6.4 M) of n-hexanol (competitive inhibitor of lipase [37][38][39][40]) plays an important role in significantly reducing lipase efficiency. Chart 1. Keeping in mind the potentials of micellar enzymology, improvement of lipase activity is indispensable in cationic w/o microemulsions.…”
Section: Introductionmentioning
confidence: 99%